DOUBLE SHACKLES AND WOMEN’S BREAKTHROUGH: A CRITICAL STUDY OF PATRIARCHY IN "LAND OF LOST SOULS" UNDER FOUCAULT’S DISCIPLINARY THEORY - Wang , Qian Qian; Raja Hassan, Tuan Rusmawati (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This paper takes the novel " Land of Lost Souls " by Malaysian writer Li Zishu as the research object, and combines Michel Foucault’s disciplinary power theory with feminist perspectives to analyze the dual oppression of women by patriarchy and social ethics and their resistance mechanisms. Through close reading of the text and critical discourse analysis, the study reveals how explicit violence and implicit discipline in the novel conspire to act on women’s bodies and identities, especially focusing on the dual marginalization of gender and disability faced by characters such as the blind girl Yinxia in the family, workplace and public sphere. The paper further explores the hidden resistance of women through deviant practices such as silence, illness, and madness, and its potential subversive significance to the power structure. This study provides an interdisciplinary analytical path for the study of Malaysian Chinese literature, and reveals the dynamics of oppression and resistance at the intersection of gender and ability from the perspective of the global South, which is enlightening for understanding the operation of structural power and the construction of subjectivity of marginalized groups.